سورۃ التکویر (آیات 11–20): کائناتی مناظرِ قیامت، نجومی قسمیں (الخُنَّسُ الجَوَارِ الكُنَّس)، لغوی و تفسیری تحقیق، اور “رسولِ کریم” کے مصداق پر علمی نقد — تفسیرِ حقانی کی روشنی میں : Surah al-Takwīr (Verses 11–20): Cosmic Scenes of the Resurrection, the Oath of the Celestial Bodies (al-khunnas al-jawāri al-kunnas), Linguistic and Exegetical Analysis, and a Critical Study of the “Noble Messenger” — in the Light of Tafsīr Ḥaqqānī - Zaheer Ud Din; Dr. Syed Naeem Badshah (Al Manhal Research Journal, 2025)
This paper offers a linguistic, exegetical, and theological study of Surah al-Takwīr (11–20), a passage that juxtaposes cosmic upheaval with oaths by celestial phenomena, culminating in an affirmation of the Qur’an’s divine authenticity. The verses portray the heavens stripped away (kushitat), Hell ignited (suʿʿirat), and Paradise drawn near (uzlifat), moments in which every soul will be confronted with its deeds. Detailed philological analysis of these terms, supported by classical lexicons and exegetical authorities, reveals the rhetorical precision and theological depth of the surah’s apocalyptic imagery. The study examines oaths by the celestial bodies—al-khunnas, al-jawāri, al-kunnas—with attention to their linguistic roots and exegetical interpretations, ranging from stars and planets to metaphors of cosmic retreat and reappearance. The phrase “wa-al-layli idhā ʿasʿasa wa-al-ṣubḥi idhā tanaffas” is analyzed through its dual lexical possibilities (night’s approach or withdrawal), reflecting the cyclical order of creation as evidence for resurrection. A central focus is the declaration “innahu la-qawlu rasūlin karīm … dhī quwwah ʿinda dhī al-ʿarshi makīn.” The study compares exegetical positions identifying the “Noble Messenger” as either Jibrīl (Gabriel) or the Prophet Muḥammad ﷺ, while affirming the Sunni theological consensus that both the words and meanings of the Qur’an are entirely divine. Sufi insights, particularly from ʿAbd al-Ḥaqq, interpret these cosmic images as metaphors for spiritual unveiling and the inner “resurrection” of the soul. Collectively, the analysis shows that this section of Surah al-Takwīr integrates cosmic disintegration, moral accountability, and the truth of revelation into a coherent theological vision: creation’s grandeur is fleeting, permanence belongs to the Hereafter, and salvation lies in monotheism, gratitude, justice, and righteous deeds through adherence to the Qur’an.